2012
DOI: 10.1007/s00464-012-2308-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of colonoscopy for colorectal cancer screening

Abstract: The results of this investigation revealed a significant incidence of colonoscopic alterations in asymptomatic people submitted to colonoscopy for colorectal cancer screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
0
4
0
3
Order By: Relevance
“…Another study reported that the incidence of bleeding was 0.30 per 1000 patient‐years, but the diagnosis of asymptomatic and complicated diverticulosis was based on questionnaires not colonoscopy. Widespread use of colonoscopy has increased the detection of incidental asymptomatic diverticulosis, and colonoscopy is the optimal method for diagnosing diverticular bleeding . Thus, colonoscopy is an essential tool for diagnosing asymptomatic and bleeding diverticula.…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that the incidence of bleeding was 0.30 per 1000 patient‐years, but the diagnosis of asymptomatic and complicated diverticulosis was based on questionnaires not colonoscopy. Widespread use of colonoscopy has increased the detection of incidental asymptomatic diverticulosis, and colonoscopy is the optimal method for diagnosing diverticular bleeding . Thus, colonoscopy is an essential tool for diagnosing asymptomatic and bleeding diverticula.…”
Section: Introductionmentioning
confidence: 99%
“…Die Prävalenz der Divertikulose liegt zwischen 28-45% in der Gesamtbevölkerung und über 60% bei den über 70jährigen [1][2][3][4][5][6]. Trotz der immensen Bedeutung des Krankheitsbildes hat es in der medizinischen Wahrnehmung im Vergleich zu anderen Krankheitsbildern bislang ein relatives Schattendasein geführt mit nur übersichtlicher Anzahl von randomisierten Therapiestudien und nur vergleichsweise wenigen Arbeiten zur Pathogenese der Erkrankung.…”
Section: Hintergrundunclassified
“…Die Prävalenz der Divertikulose wird in Studien mit verschiedenen Methoden (Endoskopie, Barium Kontrasteinlauf, Autopsie) zwischen 28 % (Screening Koloskopien; [1] (6) und 45% (Barium Kontrasteinläufen, [2][3][4][5] bis 60% bei über 70 Jährigen (Autopsiestudien [6] angegeben. Die Prävalenz der Divertikelkrankheit steigt mit dem Lebensalter an (z.B.…”
Section: Kommentar Zu Statement 37unclassified
“…Compared to other cancers where the primary goal is early detection of neoplasia, CRC can actually be prevented with detection and removal of cancer precursor lesions (Inadomi et al, 2012). It is estimated that 30% of people over the age of 50 with no history of CRC risk factors harbor adenomatous polyps (Alberti et al, 2012;Pezzoli et al, 2007), and the incidence of these polyps increases with age. Early adenoma resection is asso-ciated with considerable reductions in CRC (Rex et al, 2009;Winawer et al, 1993b), and has now been demonstrated to have mortality benefit (Zauber et al, 2012).…”
Section: Impact Of Screening On the Epidemiology Of Crcmentioning
confidence: 99%
“…Although it is difficult to identify precisely which adenomas will undergo neoplastic transformation, there are certain pathologic features that can help predict their level of risk: increased size ≥10 mm, increased number of 3 or more adenomas, villous histology, and highgrade dysplasia (Alberti et al, 2012;Lieberman et al, 2012). Most adenomas undergo a similar progression to invasive cancer termed the adenoma-carcinoma sequence (Levin et al, 2008;Sano et al, 2009).…”
Section: Impact Of Screening On the Epidemiology Of Crcmentioning
confidence: 99%